Negative electrode material and preparation method thereof, secondary battery and electric device

By pretreating and granulating the surface of the graphite material, a negative electrode material with an amorphous carbon cladding layer is formed, which solves the problem of taking into account the fast charging and cycling high-temperature performance of graphite material, and improves the stability and life of the battery.

CN119133374APending Publication Date: 2024-12-13ENVISION DYNAMICS TECH (JIANGSU) CO LTD +3

Patent Information

Application Number
CN202310694145.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Graphite negative electrode materials are difficult to have both fast charging and cycling high-temperature performance, resulting in frequent surface SEI film breaking and volume expansion, affecting the cycle stability and life of the battery.

Method used

By pretreating and granulating the surface of the graphite material, a negative electrode material including artificial graphite core and amorphous carbon coating is formed, the particle roughness and oil absorption value are controlled, structural stability is improved, and volume expansion is reduced during the cycle Stress concentration.

Benefits of technology

It achieves the consideration of fast charging and cycling performance of graphite materials, improves the overall performance and life of the battery, and is simple in process and convenient in operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133374A_ABST
    Figure CN119133374A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method thereof, a secondary battery and an electric device, and particularly relates to the technical field of secondary batteries. The negative electrode material comprises an inner core and a coating layer, the inner core comprises artificial graphite, the surface of the inner core is coated with the coating layer, and the coating layer comprises amorphous carbon; wherein the ratio of the maximum value of the variation of the radius of the negative electrode material particles every 1 degree to the maximum diameter of the particles is taken as the roughness, and the roughness of the negative electrode material particles is 0-3%. The surface of the material is pretreated, so that the material has cycle performance while improving the quick charge performance of the material, and the quick charge performance and the cycle performance of the battery can be both considered when the material is applied to the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material and a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] Graphite material has good conductivity, Li + The diffusion coefficient is large, and its good layered structure is suitable for repeated insertion and extraction of lithium ions. It is the mainstream negative electrode material for commercial lithium-ion batteries. Due to the continuous diversification of application scenarios, the market has put forward higher requirements for battery fast charging technology, and the bottleneck of fast charging lies in the negative electrode. Therefore, in order to improve the fast charging ability of the negative electrode, relevant enterprises and scientific research institutions have done a lot of research on this, for example: Patent CN107579252A uses extremely small graphite particle size to shorten the solid phase diffusion distance of lithium ions in exchange for the improvement of the fast charging ability of the material; Patent CN112582592 A uses a large coating amount to improve the lithium ion interface conduction impedance; Patent CN1691374A dissolves the coating material in a solvent and then coats it on the surface of artificial graphite. The obtained artificial graphite has a small specific surface area and a high first coulomb efficiency; Patent CN201910940312.3 uses secondary particles mixed with single particles to increase the lithium embedding end face of the material and improve the fast charging ability of the material.

[0003] At present, the means of improving the fast charging ability of graphite through small particles, large coating amount, granulation, etc. are essentially to increase the reaction active sites of the material, which can effectively improve the fast charging performance of the material, but the introduction of too many active sites increases the side reactions between the material and the electrolyte, and cannot inhibit the volume expansion of the material during the cycle, resulting in frequent breakage and formation of the surface SEI film, which is not conducive to the cycle and high temperature life, and cannot achieve both fast charging performance and cycle high temperature performance. Summary of the invention

[0004] In view of the above shortcomings of the prior art, the present invention provides a negative electrode material and a preparation method thereof, a secondary battery and an electrical device to solve the problem that graphite negative electrode materials cannot achieve both fast charging performance and high-temperature cycling performance.

[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides a negative electrode material, which includes a core and a coating layer, wherein the core includes artificial graphite, the coating layer is coated on the surface of the core, and the coating layer includes amorphous carbon; wherein the ratio of the maximum value of the change in the radius of the negative electrode material particles per 1° to the maximum diameter of the particles is taken as the roughness, and the roughness of the negative electrode material particles is 0 to 3%.

[0006] In an example of the present invention, the roughness of the negative electrode material particles is 0 to 1.5%.

[0007] In one example of the present invention, the oil absorption value of the negative electrode material is 5 to 25 cm 3 / 100g.

[0008] In one example of the present invention, the oil absorption value of the negative electrode material is 10 to 15 cm 3 / 100g.

[0009] In an example of the present invention, the structural stability parameter of the negative electrode material is 3.5 to 9.5.

[0010] In an example of the present invention, the structural stability parameter of the negative electrode material is 4.5 to 6.5.

[0011] In an example of the present invention, the particle size Dv99 of the negative electrode material is 30 to 45 μm.

[0012] In an example of the present invention, the particle size Dv99 of the negative electrode material is 32 to 38 μm.

[0013] On the other hand, the present invention provides a method for preparing a negative electrode material, which comprises at least the following steps: providing raw coke, and crushing the raw coke into aggregates of 3 to 12 μm; shaping the aggregates to obtain a precursor; graphitizing the precursor to obtain artificial graphite; mechanically fusing the artificial graphite to form physical anchor points; surface treating the artificial graphite after mechanical fusion to form chemical anchor points; granulating, depolymerizing and shaping the surface-treated material to obtain the core of the negative electrode material; coating the core of the negative electrode material with a coating agent, and obtaining the negative electrode material after demagnetization and screening.

[0014] In one example of the present invention, the aggregate is subjected to shaping treatment to obtain a precursor, wherein the feeding frequency of the shaping treatment is 60 to 80 Hz, the shaping frequency is 50 to 80 Hz, the induced draft frequency is 30 to 65 Hz, and the processing time is 6 to 15 minutes.

[0015] In one example of the present invention, in the step of subjecting the artificial graphite to mechanical fusion treatment to form a physical anchor point, the feed frequency of the mechanical fusion treatment is 30 to 50 Hz, the fusion frequency is 30 to 70 Hz, the induced draft frequency is 50 to 85 Hz, and the treatment time is 5 to 12 min.

[0016] In one example of the present invention, the fusion frequency of the mechanical fusion process is 40 to 55 Hz, the air induction frequency is 60 to 75 Hz, and the processing time is 7 to 10 minutes.

[0017] In one example of the present invention, the artificial graphite after the mechanical fusion treatment is surface treated to form chemical anchor points, including: dividing the artificial graphite after the mechanical fusion treatment into a first material and a second material of equal weight; vacuum calcining the first material at a temperature of 600 to 1500°C for 2 to 8 hours to form positively charged chemical anchor points; calcining the second material at a temperature of 500 to 1000°C in a mixed atmosphere of nitrogen and oxygen for 2 to 6 hours to form negatively charged chemical anchor points.

[0018] In one example of the present invention, the step of granulating, depolymerizing and shaping the surface-treated material to obtain the inner core of the negative electrode material includes: mixing the surface-treated first material and the second material for granulation; subjecting the material obtained after granulation to a slight depolymerization and shaping treatment, wherein the binder used for the granulation is asphalt, the softening point of the asphalt for granulation is 100 to 180°C, and the amount of the asphalt for granulation is 6% to 10% of the total mass of the first material and the second material; the depolymerization frequency of the slight depolymerization and shaping treatment is 10 to 30 Hz, and the treatment time is 1 to 3 min.

[0019] In one example of the present invention, in the step of coating the inner core of the negative electrode material with a coating agent, the coating agent is asphalt, the softening point of the coating asphalt is 30 to 150°C, and the added amount of the coating asphalt accounts for 1.8% to 7% of the total mass of the inner core material.

[0020] In one example of the present invention, the mass ratio of the granulation asphalt to the coating asphalt is 0.3 to 0.7.

[0021] In one example of the present invention, the mass ratio of the granulation asphalt to the coating asphalt is 0.4 to 0.55.

[0022] The present invention also provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate includes the above-mentioned negative electrode material, or the negative electrode material prepared by the above-mentioned preparation method.

[0023] The present invention also provides an electric device, which includes the secondary battery.

[0024] The present invention pretreats and granulates the surface of the graphite material to improve the fast charging performance of the material while improving the structural stability of the material, reduce the stress concentration caused by volume expansion during the cycle, and improve the cycle performance.

[0025] The present invention adjusts the surface characteristics of the material by reasonably controlling the process to obtain a graphite material with both fast charging capability and cycle performance, and the process is simple and easy to operate. The negative electrode material of the present invention is used in a secondary battery to achieve both fast charging performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is a flow chart of the preparation method of the negative electrode material of the present invention;

[0028] Figure 2 Flow chart of step S5 in the method for preparing the negative electrode material of the present invention. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] It should be noted that, in the absence of conflict, the features in the following examples and embodiments can be combined with each other. It should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of the present invention. The test methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0031] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.

[0032] The present invention provides a negative electrode material and a preparation method thereof, a secondary battery and an electric device. The graphite surface is pretreated and granulated by reasonably controlling the synthesis process, so that the fast charging performance is improved while the cycle performance is also achieved.

[0033] The negative electrode material of the present invention comprises a core and a coating layer, wherein the core comprises artificial graphite; the coating layer is coated on the surface of the core, and the coating layer comprises amorphous carbon. Amorphous carbon has a disordered structure and a high interlayer spacing. The use of amorphous carbon to coat artificial graphite can enable active ions to diffuse faster in the negative electrode active material particles, thereby improving the rapid charging capability of the material. At the same time, the amorphous carbon coating layer can also protect the artificial graphite core, greatly reducing the peeling of the graphite layer caused by the co-embedding of the solvent in the artificial graphite, so that the negative electrode active material has a higher structural stability.

[0034] The ratio of the maximum value of the change in the radius of the negative electrode material particle per 1° to the maximum diameter of the negative electrode material particle is defined as the roughness, and the roughness of the negative electrode material particles of the present invention is 0 to 3%, for example, 1%, 2%, 3%, etc. When the roughness meets this range, it is beneficial to form physical anchor points on the surface of the material that can be embedded with each other, enhance the structural stability of the secondary particle material, reduce the stress concentration caused by volume expansion during the cycle, and improve the cycle performance; when the roughness is higher than this range, it will reduce the stability of the secondary particle structure and deteriorate the cycle performance. Further, the roughness is 0 to 1.5%. For example, 0.1%, 0.5%, 0.8%, 1.3% or 1.5%, etc. The roughness of the negative electrode material particles can be adjusted by shaping and cutting the graphitized particles.

[0035] In some embodiments, the oil absorption value of the negative electrode material is 5 to 25 cm 3 / 100g, for example 5cm 3 / 100g、10cm 3 / 100g、15cm 3 / 100g、20cm 3 / 100g、25cm 3 / 100g, etc. When the oil absorption value of the negative electrode material meets this range, it is conducive to the formation of electrically affinitive chemical sites on the material surface, enhancing the structural stability of the secondary particle material, reducing the stress concentration caused by volume expansion during the cycle, and improving the cycle performance; at the same time, it enhances the affinity of the graphite surface to the coating layer, facilitates the formation of a uniform and thin coating layer, and enhances the fast charging performance; if the oil absorption value of the negative electrode material is higher than this range, it means that there are too many fine powders, which will deteriorate the high-temperature cycle and storage performance; if the oil absorption value of the negative electrode material is lower than this range, it means that the coating effect of the material is too poor, which will deteriorate the kinetics. Furthermore, the oil absorption value of the negative electrode material is 10 to 15cm 3 / 100g, for example 11cm 3 / 100g、12cm 3 / 100g、13cm 3 / 100g or 14cm 3 / 100g, etc. The oil absorption value of the negative electrode material is adjusted by surface treatment of the material after shaping and cutting.

[0036] In some embodiments, the structural stability parameter of the negative electrode material is 3.5 to 9.5, such as 3.5, 5.5, 7.5 or 9.5, etc. At this time, the isotropy of the material can be taken into account to improve the fast charging performance, and at the same time, the gaps between the negative electrode material particles can be ensured to be within a reasonable range for the infiltration of the electrolyte. If the structural stability parameter is lower than the above range, the structural stability of the material is poor, which is not conducive to long-term cycling in the entire range; if the structural stability parameter is higher than this range, it means that the gaps between the material particles are small, which aggravates stress concentration and the difficulty of electrolyte infiltration, and worsens the dynamics. Furthermore, the structural stability parameter of the negative electrode material is 4.5 to 6.5, such as 4.5, 5.0, 6.0 or 6.5, etc.

[0037] It should be noted that the surface roughness test is: the point that bisects the longest diameter of the particle (the longest diameter of the particle) measured by shape is defined as the center, and the distance from the center to each point on the particle surface is calculated as the particle radius; the change in the particle radius per 1° (1° rotation around the center) is an absolute value, and its maximum value refers to the maximum value of the change per 1° rotation measured for the entire circumference of the particle; then (surface roughness) = {(the maximum value of the change in the particle radius per 1°) / (the longest diameter of the particle)}.

[0038] Oil absorption value test: refer to the national standard GB / T 3780.2-2003, in which linseed oil is used as the test solvent.

[0039] Structural stability parameter test: Referring to the national standard GB / T24533-2019, the powder sample is pressed into a tablet. Before the test, the standard pressure 2T is maintained for 20S. After the pressure is released, the pressure is maintained at 5T for 20S after an interval of 10min. The formal operation starts after the pressure release interval of 10min. The 5T powder pressure is measured as P0, and then the powder is tested at a pressure of 5.5, 6, 6.5...5+0.5n. The compactions are recorded as P1, P2, P3...Pn respectively. When Pn / Pn-1≥1.05, this Pn is called the particle structure failure compaction, and the structural stability parameter S=5+0.5n / 5.

[0040] See also Figure 1 The method for preparing the negative electrode material of the present invention comprises at least the following steps:

[0041] S1. providing raw coke, and crushing the raw coke into aggregates of 3 μm to 12 μm;

[0042] S2, shaping the aggregate to obtain a precursor;

[0043] S3, graphitizing the precursor to obtain artificial graphite;

[0044] S4, performing mechanical fusion treatment on the artificial graphite to form a physical anchor point;

[0045] S5, performing surface treatment on the artificial graphite after the mechanical fusion treatment to form chemical anchor points;

[0046] S6, granulating, depolymerizing and shaping the surface-treated material to obtain the core of the negative electrode material;

[0047] S7. Coating the inner core of the negative electrode material with a coating agent, and obtaining the negative electrode material after demagnetization and screening.

[0048] Specifically, the raw coke in step S1 can be directly purchased through conventional commercial channels. The raw coke can be selected from conventional coke materials in the field. For example, the raw coke includes one or more of metallurgical coke, petroleum coke, asphalt coke, needle coke, soft carbon and hard carbon precursors, that is, the raw coke can be selected from any one of the raw cokes listed above, for example, metallurgical coke; or petroleum coke; or asphalt coke, etc.; any two or more of the raw cokes listed above can also be selected as a combination mixed in any proportion, for example, a combination of metallurgical coke and petroleum coke; or a combination of asphalt coke and needle coke; or a combination of soft carbon and hard carbon precursors; or metallurgical coke. Compositions of petroleum coke and asphalt coke, etc. are not listed here one by one. Of course, the raw coke can also be selected from the types of materials not listed above.

[0049] In some embodiments, the volatile content of the raw coke selected in step S1 is 5% to 15%, for example, the volatile content of the raw coke can be 5%, 8%, 10%, 12% or 15%, etc.; further, the volatile content of the raw coke is 6% to 10%, for example, 6%, 7% or 9%, etc. The volatile content of the raw coke is appropriate, so that the prepared artificial graphite has a higher structural strength. The volatile content of the raw coke can be tested by methods known in the art. For example, it is measured with reference to SHIT 0026-1990.

[0050] Step S1: crushing the raw coke, which can be done by conventional equipment and methods in the art, such as air jet mill, mechanical mill or roller mill, etc. The large pieces of raw coke are crushed into aggregates of 3 to 12 μm by crushing, so as to facilitate the subsequent shaping process. Further, the raw coke is crushed into aggregates of 6 to 10 μm, such as 6 μm, 8 μm, 10 μm, etc.

[0051] Step S2 is to shape the aggregate obtained in step S1 to grind the edges and corners of the aggregate particles and remove fine powder. The greater the shaping degree, the closer the particles are to spherical. The shaping process is also beneficial to the subsequent granulation process, so that the secondary particles in the negative electrode material have higher structural stability.

[0052] Step S2 uses equipment and methods known in the art to shape the aggregate, such as a shaping machine or other shaping equipment. The feeding frequency during shaping is 60 to 80 Hz, such as 60 Hz, 70 Hz or 80 Hz, and the shaping frequency is 50 to 80 Hz, such as 50 Hz, 60 Hz, 70 Hz or 80 Hz; the induced draft frequency is 30 to 65 Hz, such as 30 Hz, 40 Hz, 50 Hz or 60 Hz, and the shaping time is 6 to 15 min, such as 6 min, 9 min, 12 min or 15 min, and the like.

[0053] Step S3 is to graphitize the material obtained in step S2 under high temperature conditions to obtain artificial graphite with a certain degree of graphitization. The graphitization treatment is performed using equipment known in the art, such as a graphitization furnace. In some embodiments, the temperature of the graphitization treatment is 2800° C. to 3200° C., and the temperature of the further graphitization treatment is 2900° C. to 3100° C., and further, the temperature of the graphitization treatment is 3000° C.

[0054] Step S4 performs mechanical fusion treatment on the artificial graphite obtained in step S3 to form physical anchor points on the graphite surface, enhance the structural stability of the material, reduce stress concentration caused by volume expansion during the cycle, and improve cycle performance.

[0055] Mechanical fusion treatment is carried out using equipment known in the art, such as a fusion machine, etc. The feeding frequency during mechanical fusion treatment is 30 to 50 Hz, such as 40 Hz; the fusion frequency is 30 to 70 Hz, further, the fusion frequency is 40 to 55 Hz, such as 40 Hz, 50 Hz, 55 Hz, etc.; the induced air frequency is 50 to 85 Hz, further, 60 to 75 Hz, such as 60 Hz, 70 Hz, 75 Hz, etc.; the mechanical fusion treatment time is 5 to 12 minutes, further 7 to 10 minutes, such as 7 minutes, 8 minutes or 10 minutes, etc.

[0056] Step S5 performs surface treatment on the material obtained in step S4 to form chemical anchor points. Step S5 specifically includes the following steps:

[0057] S51, dividing the artificial graphite after mechanical fusion treatment into a first material and a second material.

[0058] The material obtained in step S4 is divided into two parts, which are respectively recorded as the first material and the second material. The first material and the second material may be of equal weight or unequal weight. Preferably, the first material and the second material are of equal weight.

[0059] S52, calcining the first material at a temperature of 600 to 1500° C. for 2 to 8 hours in vacuum to form positively charged chemical anchor points.

[0060] The first material is placed in a vacuum furnace and vacuum-baked at a temperature of 600 to 1500° C. for 2 to 8 hours. In some embodiments, the vacuum-baked temperature may be 600° C., 900° C., 1200° C., or 1500° C., and the vacuum-baked time may be 2 hours, 4 hours, 6 hours, or 8 hours. After the calcination, positively charged chemical anchor points are formed on the surface of the first material.

[0061] S53, calcining the second material at a temperature of 500 to 1000° C. in a mixed atmosphere of nitrogen and oxygen for 2 to 6 hours to form negatively charged chemical anchor points.

[0062] The second material is placed in an atmosphere furnace, and a mixture of nitrogen and oxygen is introduced into the furnace, and calcined at a temperature of 500 to 1000°C for 2 to 6 hours. Among them, in the mixture of nitrogen and oxygen introduced into the furnace, the volume proportion of oxygen is 2% to 12%, preferably 5% to 8%, for example, the volume proportion of oxygen can be 5%, 7% or 8%, etc. The calcination temperature of the second material is preferably 800 to 1200°C, for example, it can be 800°C, 1000°C or 1200°C, etc. The calcination time of the second material can be, for example, 2h, 4h or 6h, etc. After the calcination is completed, negatively charged chemical anchor points are formed on the material surface of the second material.

[0063] Step S6: The first material and the second material of step S5 are mixed and granulated so as to aggregate the independently dispersed primary particles to form secondary particles, so that the isotropy of the negative electrode material is improved and the negative electrode material has better structural stability.

[0064] The amount of the binder added during the granulation process accounts for 6% to 10% of the total mass of the first material and the second material, for example, 6%, 8% or 10%, etc. The binder can be any conventional binder in the art, preferably asphalt, and the softening point of the asphalt used for granulation is 100 to 180°C, for example, 120°C, 140°C or 160°C, etc.

[0065] The granulation in step S6 can be carried out using equipment known in the art, such as a granulator. The granulator generally includes a stirred reactor and a module for temperature control of the reactor. By regulating the stirring speed, heating rate, granulation temperature, cooling rate, etc. during the granulation process, the granulation degree and the structural strength of the particles can be regulated, thereby facilitating the obtained negative electrode active material to have a higher gram capacity while also having a higher structural stability. The structural stability parameter of the material of the present invention after granulation is between 3.5 and 9.5, preferably between 4.5 and 6.5.

[0066] During the granulation process, the particles tend to agglomerate to form oversized particles. Therefore, after the granulation is completed, the product needs to be depolymerized and shaped to prevent the oversized particles from affecting the material processing performance. Among them, the depolymerization and shaping are processed using equipment known in the art, such as a disintegrator, a shaping machine, etc. The depolymerization frequency of the depolymerization and shaping is 10 to 30 Hz, such as 10 Hz, 20 Hz or 30 Hz, and the depolymerization treatment time is 1 to 2 min, such as 1 min, 2 min or 3 min, etc.; the shaping frequency during the shaping process is 5 to 25 Hz, such as 5 Hz, 10 Hz, 15 Hz or 25 Hz, etc., and the treatment time is 1 to 3 min, such as 2 min, etc. After the depolymerization and shaping is completed, the artificial graphite that meets the requirements is obtained as the core of the negative electrode material.

[0067] Step S7 is to coat the artificial graphite kernel of step S6. The coating agent can be selected from an organic carbon source, and the coating agent includes but is not limited to asphalt, liquid tar, liquid resin, solid resin, etc. It is preferably asphalt, and the softening point of the coating asphalt is 30 to 150°C, such as 30°C, 50°C, 100°C or 150°C. The amount of coating asphalt added is 1.8% to 7% of the mass of the artificial graphite kernel, such as 2%, 4%, 6% or 7%, etc.; further, the ratio of the granulation asphalt in step S6 to the coating asphalt in step S7 is controlled between 0.3 and 0.7, preferably 0.4 to 0.55, such as 0.4, 0.5 or 0.55, etc.

[0068] The coating process can refer to the conventional method in the art, that is, the artificial graphite core is mixed with the coating agent, and carbonized at a certain temperature, and the carbonization temperature can be 900 to 1400° C., for example, 1000° C., 1100° C., 1200° C., 1300° C., etc. The ratio of the coating agent to the artificial graphite can be set according to the conventional ratio.

[0069] After coating, the product needs to be demagnetized and screened to obtain negative electrode materials with suitable particle size distribution. The specific demagnetization screening includes: first demagnetizing the coated material; screening with a screen to control the particle size Dv99 of the material to 30 to 45 μm, preferably 32 to 38 μm, for example, 32 μm, 35 μm or 38 μm. After screening, the negative electrode material that meets the requirements can be obtained.

[0070] In this application, Dv99 of the negative electrode material has a well-known meaning in the art and can be tested by methods known in the art. For example, it can be measured with a laser particle size analyzer (such as MalvernMastersizer 3000) with reference to the standard GB / T 19077.1-2016. Dv99 represents the particle size value corresponding to when the volume cumulative distribution percentage reaches 99%, and its physical meaning is that particles with a particle size smaller than it account for 99%.

[0071] The present invention provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet includes the negative electrode material of the present invention. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet; the separator separates the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet. The secondary battery of the present invention includes the negative electrode material of the present invention, which can significantly improve the fast charging capability of the high SOC state and greatly shorten the charging time of the battery.

[0072] Specifically, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode current collector has a material with good electrical conductivity and mechanical strength, and plays the role of conducting electricity and collecting current. The negative electrode current collector can adopt the conventional current collector type of the present invention, such as copper foil. The negative electrode active material layer can be disposed on one surface of the negative electrode current collector, or on both surfaces of the negative electrode current collector. The negative electrode active material layer also includes a conductive agent, a binder and a thickener. The conductive agent, the binder and the thickener can all be selected from conventional material types in the art. As an example, the conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR) or a combination thereof mixed in any proportion; the thickener is selected from carboxymethyl cellulose (CMC), which may be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).

[0073] The negative electrode sheet can be prepared according to methods known in the art. For example, the negative electrode material, binder, thickener and conductive agent are dispersed in deionized water to form a uniform negative electrode slurry: the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet is obtained. Among them, the ratio between the components in the negative electrode slurry can be set according to the conventional ratio, and is not limited here.

[0074] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode current collector can be made of a material with good conductivity and mechanical strength, such as aluminum foil. The positive electrode active material layer includes a positive electrode material, a conductive agent and a binder. The specific type of the positive electrode material is not specifically limited here. The materials known in the art that can be used for the positive electrode of a secondary battery can be used. Those skilled in the art can choose according to actual needs. For example, if the secondary battery is a lithium-ion secondary battery, the positive electrode material may include a lithium transition metal oxide or a lithium-containing phosphate. Specifically, the lithium transition metal oxide includes but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel oxide, lithium cobalt oxide, lithium nickel cobalt oxide, etc.; lithium-containing phosphates include but are not limited to lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The positive electrode binder can be selected from conventional binder types in the art, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc. The positive electrode conductive agent is one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion.

[0075] The positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode material, the conductive agent and the binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry: the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained. The ratio between the components in the positive electrode slurry can be set with reference to the conventional ratio, and is not limited here.

[0076] The diaphragm is selected from conventional types in the art, for example, a PE porous membrane is selected as the diaphragm, the thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0077] The electrolyte is selected from a conventional combination type in the art, which includes an organic solvent, an electrolyte salt (selected according to the type of battery, for example, a lithium salt is selected for a lithium battery) and an additive, wherein the solvent can be selected from one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), etc., or a mixture of several of them in any proportion. The lithium salt is selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalate phosphate), LiTFOP (lithium tetrafluorooxalate phosphate) or a combination thereof in any proportion. The additive may include a film-forming additive and a functional additive that can improve battery performance. The specific types of additives are not described one by one here, and those skilled in the art may select according to actual needs.

[0078] The present invention also provides an electric device, which comprises the secondary battery of the present invention. The secondary battery can be used as a power source of the electric device or as an energy storage unit of the electric device.

[0079] The above-mentioned electrical devices may be vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, electric tools, etc. Vehicles may be fuel vehicles, gas vehicles or new energy vehicles, and new energy vehicles may be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.; spacecraft include airplanes, rockets, space shuttles and spacecraft, etc.; electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc.; electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. This application does not impose any special restrictions on the above-mentioned electrical devices.

[0080] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available. The parameters of the following examples are shown in Table 1.

[0081] Example 1

[0082] Step 1: crushing raw materials: selecting raw coke with volatile matter of 8% for crushing into 8μm aggregates;

[0083] Step 2: Shaping and removing fine powder: The aggregate obtained in step 1 is shaped and removed to remove fine powder, the feeding frequency is 70 Hz, the shaping frequency is 65 Hz, the induced draft frequency is 45 Hz, and the treatment time is 10 minutes;

[0084] Step 3: Graphitization treatment: graphitizing the material obtained in step 2 at a high temperature of 3000°C;

[0085] Step 4: Mechanical fusion: The material obtained in step 3 is subjected to mechanical fusion treatment to form a physical anchor point, wherein the feeding frequency is 40 Hz, the fusion frequency is 45 Hz, the induced air frequency is 65 Hz, and the treatment time is 8 minutes;

[0086] Step 5, surface treatment: first, the material obtained in step 4 is divided into a first material and a second material of equal weight; the first material is vacuum-baked at 900° C. for 4 hours to form a positively charged chemical anchor point; the second material is calcined at 700° C. in a nitrogen and oxygen mixed atmosphere (oxygen accounts for 6%) for 3 hours to form a negatively charged chemical anchor point;

[0087] Step 6, granulation: the first material and the second material obtained in step 5 are granulated, and the granulating agent is asphalt with a softening point of 130°C, and the addition amount accounts for 8% of the total mass of the first material and the second material; after the granulation is completed, the granulated product is slightly depolymerized and shaped, wherein the depolymerization frequency is 20Hz, the treatment is 2min, and the shaping frequency is 15Hz, and the treatment is 2min;

[0088] Step 7, coating: coating the material obtained in step 6, using asphalt with a softening point of 80°C as the coating agent, the addition amount accounts for 4% of the mass of the material in step 6, and the ratio of asphalt for granulation to asphalt for coating should be controlled to be 0.5;

[0089] Step 8: After coating, the product is demagnetized and sieved to control the particle size Dv99 of the obtained material to 36 μm.

[0090] Example 2

[0091] The difference between this embodiment and embodiment 1 is that the volatile matter of the raw coke selected in step 1 is 6%.

[0092] Example 3

[0093] The difference between this embodiment and embodiment 1 is that the fusion frequency during the mechanical fusion process in step 4 is 60 Hz, and the induced draft frequency is 80 Hz.

[0094] Example 4

[0095] The difference between this embodiment and embodiment 1 is that the fusion frequency during the mechanical fusion process in step 4 is 35 Hz, and the induced draft frequency is 55 Hz.

[0096] Example 5

[0097] The difference between this embodiment and embodiment 1 is that the temperature of vacuum calcining the first material in step 5 is 700°C.

[0098] Example 6

[0099] The difference between this embodiment and embodiment 1 is that the atmosphere for calcining the second material in step 5 is a nitrogen-oxygen mixed gas (oxygen accounts for 6%), and the calcination temperature is 600°C.

[0100] Example 7

[0101] The difference between this embodiment and embodiment 1 is that the atmosphere for calcining the second material in step 5 is a nitrogen-oxygen mixed gas (oxygen accounts for 6%), and the calcination temperature is 900°C.

[0102] Example 8

[0103] The difference between this embodiment and embodiment 1 is that the atmosphere for calcining the second material in step 5 is a nitrogen-oxygen mixed gas (oxygen accounts for 4%), and the calcination temperature is 700°C.

[0104] Example 9

[0105] The difference between this embodiment and embodiment 1 is that the atmosphere for calcining the second material in step 5 is a nitrogen-oxygen mixed gas (oxygen accounts for 10%), and the calcination temperature is 700°C.

[0106] Example 10

[0107] The difference between this embodiment and embodiment 1 is that the softening zone of the asphalt for granulation in step six is ​​160°C.

[0108] Embodiment 11

[0109] The difference between this embodiment and embodiment 1 is that in the slight depolymerization and shaping process in step six, the depolymerization frequency is 25 Hz and the shaping frequency is 20 Hz.

[0110] Example 12

[0111] The difference between this embodiment and embodiment 1 is that the softening point of the coating asphalt in step seven is 120°C.

[0112] Embodiment 13

[0113] The difference between this embodiment and embodiment 1 is that the mass ratio of coating asphalt to granulation asphalt in step seven is 0.65.

[0114] Comparative Example 1

[0115] The difference between this comparative example and Example 1 is that the volatile matter of the raw coke is 3%.

[0116] Comparative Example 2

[0117] The difference between this comparative example and Example 1 is that the fusion frequency in step 4 is 90 Hz and the induced draft frequency is 80 Hz.

[0118] Comparative Example 3

[0119] The difference between this comparative example and Example 1 is that the fusion frequency in step 4 is 10 Hz and the induced draft frequency is 10 Hz.

[0120] Comparative Example 4

[0121] The difference between this comparative example and Example 1 is that step five is not performed.

[0122] Comparative Example 5

[0123] The difference between this comparative example and Example 1 is that the softening point temperature of the asphalt used for granulation in step 6 is 250°C.

[0124] Comparative Example 6

[0125] The difference between this comparative example and Example 1 is that the softening point temperature of the coating asphalt in step seven is 200°C.

[0126] Comparative Example 7

[0127] The difference between this comparative example and Example 1 is that the mass ratio of coating asphalt to granulation asphalt in step seven is 1.

[0128] The negative electrode materials prepared in Examples 1 to 13 and Comparative Examples 1 to 7 were respectively assembled into secondary batteries according to the following method.

[0129] Preparation of positive electrode sheet: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.5:1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through processes such as drying, cold pressing, and slitting.

[0130] Preparation of negative electrode sheets: Mix the negative electrode material prepared above, conductive agent acetylene black, thickener CMC, and binder SBR in a mass ratio of 96.4:1:1.2:1.4, add solvent deionized water, stir and mix thoroughly to obtain negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode collector copper foil, and prepare the positive electrode sheet through drying, cold pressing, slitting and other processes.

[0131] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0132] Preparation of the diaphragm: A PE porous membrane with a thickness of 11 um is used as the diaphragm, wherein the air permeability is 180 s / 100 mL to 380 s / 100 mL; and the porosity is 30% to 50%.

[0133] Battery assembly: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then, the aluminum plastic film is wrapped, and after drying, the prepared electrolyte is injected. After packaging, standing, and formation, a soft-pack battery with a capacity of 1Ah (i.e., lithium-ion secondary battery) is finally prepared.

[0134] The secondary batteries prepared above were subjected to performance tests respectively. The test results are shown in Table 2 and Table 3. The test methods are as follows:

[0135] (1) Cyclic capacity retention test method

[0136] At 25°C, the material is cycled at 0.21A / g (calculated based on the mass of the positive electrode material) and 2.8-4.25V. The number of cycles when the initial capacity reaches 80% is recorded as the material cycle capacity evaluation number.

[0137] (2) Fast charging time test method

[0138] The battery cell is directly charged to 8% SOC state with 0.33C current, and then the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80% are tested according to the three-electrode window of the battery cell, which are C1, C2, C3, C4, C5, C6, C7, and C8 respectively. Step charge is used to charge to 80%, that is, 8%-10% is charged with C1, 10% to 20% is charged with C2, and so on. The charging time from 8% to 80% SOC state is recorded as the measure of fast charging capability. The calculation formula is:

[0139] T=(0.02 / C1+0.1 / C2+0.1 / C3+0.1 / C4+0.1 / C5+0.1 / C6+0.1 / C7+0.1 / C8)*60.

[0140] (3) Storage performance test

[0141] At 25℃, the capacity is fixed with a current of 0.33C and recorded as C0. Then the battery cells are stored at a high temperature of 60℃. After that, the battery cells are taken out every 7 days and the capacity is tested at room temperature and recorded as C1, C2, Cn. The number of days when Cn reaches 80% of C0 is used as a measure of the storage capacity.

[0142] (4) Surface roughness test

[0143] The point where the longest diameter of the particle (the longest diameter of the particle) measured by shape is divided into two equal parts is defined as the center, and the distance from the center to each point around the particle is calculated. The change in the particle radius per 1° is an absolute value, and its maximum value refers to the maximum value of the change per 1° measured for the entire circumference of the particle, (surface roughness) = {(the maximum value of the change in the particle radius per 1°) / (the longest diameter of the particle)}.

[0144] (5) Oil absorption value test

[0145] Refer to the national standard GB / T 3780.2-2003, in which linseed oil is used as the test solvent.

[0146] (6) Structural stability parameter test

[0147] According to the national standard GB / T24533-2019, the powder sample is pressed into a sheet. Before the test, the standard pressure of 2T is maintained for 20S. After the pressure is released, the pressure is maintained at 5T for 20S after an interval of 10min. The formal operation begins after the pressure is released for 10min. The 5T powder pressure is measured as P0, and then 5.5, 6, 6.5...5+0.5n. The powder is pressure tested, and the compaction is recorded as P1, P2, P3...Pn. When Pn / Pn-1≥1.05, this Pn is called the particle structure failure compaction, and the structural stability parameter S=5+0.5n / 5.

[0148] Table 1: Process parameters of Examples 1 to 13 and Comparative Examples 1 to 7

[0149]

[0150] Table 2: Physical properties of Examples 1 to 13 and Comparative Examples 1 to 7

[0151]

[0152] It should be noted that Dv50 in Table 2 represents the particle size value corresponding to when the volume cumulative distribution percentage reaches 50%. Its physical meaning is that particles with a particle size smaller than it account for 50%.

[0153] Particle size ratio: refers to the ratio of the specific surface area to volume of the negative electrode material particles.

[0154] Tap density: Under certain conditions, the mass per unit volume of the powder in the container measured after being vibrated.

[0155] Table 2 shows that the particle size ratio of the negative electrode material prepared in this application is 2.2-3.8 (1 / cm), and the tap density is 0.95-1.12 g / cm 3 .

[0156] Table 3: Electrical properties of Examples 1 to 13 and Comparative Examples 1 to 7

[0157]

[0158] Table 3 shows that the negative electrode material prepared in the present invention is assembled into a battery, and it only takes 16 to 20 minutes to charge it from 8% SOC to 80% SOC; it is cycled using a 2.8 to 4.25V charge and discharge system, and when the initial capacity is 80%, the number of cycles can reach 3100 to 4300.

[0159] It can be concluded from Tables 1 to 3 that: By comparing Examples 1 to 2 and Comparative Example 1, it can be found that the reduction of volatile matter in the raw coke reduces the roughness of the finished material. As the volatile matter decreases, the self-adhesiveness of the material deteriorates, making it easier to process, while the structural stability of the secondary particles deteriorates, worsening the material's cyclic stability.

[0160] By comparing Examples 1, 3, 4 and Comparative Examples 2 and 3, it can be found that the change in fusion frequency significantly changes the oil absorption value of the finished material and changes the material structure stability parameters. This is because the fusion frequency will affect the surface physical state of graphite, and the frequency is proportional to the physical anchor points on its surface. The more physical anchor points there are, the easier it is for graphite aggregates to physically interlock, which facilitates granulation and improves graphite dynamics. At the same time, physical interlocking enhances the stability of the graphite structure and inhibits the deterioration of life caused by cyclic expansion.

[0161] By comparing Example 1, Examples 5 to 10 and Comparative Example 4, it can be found that changes in high-temperature treatment conditions will significantly change the stability parameters and particle size of the finished material. This is because the high-temperature treatment conditions affect the chemical state of the graphite surface, and the temperature is proportional to the chemical anchor points on its surface. The higher the temperature and the more chemical anchor points there are, the easier it is for the graphite aggregate to chemically electrostatically intercalate, which facilitates granulation and improves graphite dynamics. At the same time, chemical electrostatic intercalation enhances the stability of the graphite structure and inhibits the deterioration of its life caused by cyclic expansion.

[0162] By comparing Example 1, Examples 11 to 13 and Comparative Examples 5 to 7, it can be found that changing the softening point of asphalt and the usage ratio of granulated asphalt to coated asphalt significantly changes the structural stability parameters and particle size. This is because the softening point of granulated asphalt affects the granulation effect. A relatively low softening point leads to good aggregate orientation in granulation. The softening point and usage ratio of coated asphalt affect the coating effect. A relatively low softening point and a reasonable usage ratio can ensure that the coating layer is thin and uniform, thereby optimizing the fast charging performance, cycling performance and high-temperature storage performance of the material.

[0163] The present invention pre-treats and granulates the surface of the graphite material by reasonably controlling the process, thereby improving the fast charging performance of the material and the structural stability of the material, and the process is simple and easy to operate. The negative electrode material of the present invention is used in a secondary battery, which can achieve both fast charging performance and cycle performance of the battery. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.

[0164] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A negative electrode material, It is characterized in that include: a core including artificial graphite; A coating layer, coated on the surface of the core, wherein the coating layer comprises amorphous carbon; The ratio of the maximum value of the change in radius of the negative electrode material particles per 1° to the maximum diameter of the particles is taken as the roughness, and the roughness of the negative electrode material particles is 0 to 3%.

2. The negative electrode material according to claim 1, It is characterized in that The roughness of the negative electrode material particles is 0 to 1.5%.

3. The negative electrode material according to claim 1, It is characterized in that The oil absorption value of the negative electrode material is 5 to 25 cm 3 / 100g.

4. The negative electrode material according to any one of claims 1 to 3, It is characterized in that The structural stability parameter of the negative electrode material is 3.5 to 9.

5.

5. A method for preparing the negative electrode material according to any one of claims 1 to 4, It is characterized in that At least the following steps are included: Providing raw coke, and crushing the raw coke into aggregates of 3 μm to 12 μm; The aggregate is subjected to shaping treatment to obtain a precursor; The precursor is graphitized to obtain artificial graphite; Performing mechanical fusion treatment on the artificial graphite to form a physical anchor point; The artificial graphite after mechanical fusion treatment is subjected to surface treatment to form chemical anchor points; Granulating, depolymerizing and shaping the surface-treated material to obtain the core of the negative electrode material; The inner core of the negative electrode material is coated with a coating agent, and after demagnetization and screening, the negative electrode material is obtained.

6. The preparation method according to claim 5, It is characterized in that In the step of shaping the aggregate to obtain a precursor, the feeding frequency of the shaping process is 60 to 80 Hz, the shaping frequency is 50 to 80 Hz, the induced draft frequency is 30 to 65 Hz, and the processing time is 6 to 15 minutes.

7. The preparation method according to claim 5, It is characterized in that In the step of mechanically fusing the artificial graphite to form physical anchor points, the feeding frequency of the mechanical fusion treatment is 30 to 50 Hz, the fusion frequency is 30 to 70 Hz, the induced draft frequency is 50 to 85 Hz, and the treatment time is 5 to 12 minutes.

8. The preparation method according to claim 5, It is characterized in that The artificial graphite after mechanical fusion treatment is subjected to surface treatment to form chemical anchor points, including: dividing the artificial graphite after the mechanical fusion treatment into a first material and a second material; The first material is vacuum-baked at a temperature of 600 to 1500° C. for 2 to 8 hours to form a positively charged chemical anchor point; The second material is calcined at a temperature of 500 to 1000° C. in a mixed atmosphere of nitrogen and oxygen for 2 to 6 hours to form negatively charged chemical anchor points.

9. The preparation method according to claim 8, It is characterized in that The step of granulating, depolymerizing and shaping the surface-treated material to obtain the inner core of the negative electrode material comprises: The surface-treated first material and the second material are mixed for granulation, wherein the binder used in the granulation is asphalt, the softening point of the asphalt used for granulation is 100 to 180° C., and the amount of the asphalt used for granulation accounts for 6% to 10% of the total mass of the first material and the second material; The material obtained after granulation is subjected to slight depolymerization and shaping treatment, wherein the depolymerization frequency is 10 to 30 Hz, the treatment time is 1 to 3 minutes, and the shaping frequency is 5 to 25 Hz, and the treatment time is 1 to 3 minutes.

10. The preparation method according to claim 9, It is characterized in that In the step of coating the inner core of the negative electrode material with a coating agent, the coating agent is asphalt, the softening point of the coating asphalt is 30 to 150° C., and the added amount of the coating asphalt accounts for 1.8% to 7% of the total mass of the inner core material.

11. The preparation method according to claim 10, It is characterized in that The mass ratio of the granulation asphalt to the coating asphalt is 0.3 to 0.

7.

12. A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, It is characterized in that The negative electrode plate comprises the negative electrode material according to any one of claims 1 to 4, or the negative electrode material prepared by the preparation method according to any one of claims 5 to 11.

13. An electrical device, It is characterized in that Includes the secondary battery as claimed in claim 12.

Citation Information

Patent Citations

  • Preparation method of high-power carbon-coated synthetic graphite negative electrode material

    CN107579252A

  • Artificial graphite negative-pole material, preparation method therefor and lithium-ion battery

    CN110642247A

  • High-compaction quick-charging artificial graphite material and preparation method thereof

    CN112582592A

  • Method for preparing artificial graphite cathode material of lithium ion battery

    CN1691374A

Cited By

  • A method for delaying the preparation of high-multiplying artificial graphite negative electrode material from petroleum coke

    CN122771376A